(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Authors distinguished 31 key areas of the national and 65 ones of regional level for the region territory. Their plant cover is various and represented by zone types of vegetation. It is identified that the rare fund of key areas of the national level counts 132 associations, and of the regional level are 100 associations. Rare associations were analysed by character of associatedness of populations in community, autosozological significance of dominants, botany-geographical significance, sozological status and was made sozological categorization. It is defined that physical vanishing, environment change and contamination are the principal threats for rarity phytodiversity.